A Preliminary Study of 3D Vernacular Documentation for Conservation and Evaluation: A Case Study in Keraton Kasepuhan Cirebon - Shafarina Wahyu Trisyanti; Deni Suwardhi; Iwan Purnama; Ketut Wikantika (Buildings, 2023)
Despite the wealth of cultural heritage objects in Indonesia, some of which are considered UNESCO World Heritage sites, more documentation still needs to be done. One of the reasons behind this problem is that the documentation of complex cultural heritage objects is more complicated than most modern objects, which are often more simplistic. This preliminary study aimed to document vernacular heritage buildings in 3D to be used as a conservation and building management tool. The built digital model can then be used as a building assessment tool. The data acquisition method used in this study was a combination of photogrammetry and laser scanner technology. The building model was stored as BIM (IFC model) and then georeferenced before being converted to IndoorGML. The building elements’ information contained in the building model was retrieved as input to analyze the building. This research included analyses for building assessment, natural room temperature, natural lighting, and indoor space and relation. All results from the analysis were used as input to calculate the reliability value of the building using the AHP method. The case study for the heritage building was the house of Prince Arya Denda at Kasepuhan Palace, Cirebon, Indonesia.